DUALISME HUKUM NIKAH SIRRI DI INDONESIA DALAM PERSPEKTIF FIQIH INDONESIA (Refleksi 41 Tahun Undang-Undang No. 1 Tahun 1974 tentang Perkawinan) - Amin, Moh (Analisis: Jurnal Studi Keislaman, 2015)
THE  DUALISM  OF UNREGISTERED  MARRIAGE  LAW IN INDONESIA IN INDONESIAN FIQH PERSPECTIVE (THE REFLECTION ON 41 YEAR OF LAW NO 1 OF 1974 ON MARRIAGE):  This paper examines  about  the legal dualism of unregistered  marriages  in  this  country  which  doesn’t  over 41 years after the enactment  of Law No 1 year 1974 about marriage by emphasizing on Indonesia Fiqh approach as the method of the analysis. The result  of the  study  found that  the  perspective  of Indonesian  Fiqh is the fulfillment  of the first  obligation  which is the responsibility  the obligation to fulfill the obligation of the first pillar and marriage according to the religious requirements as defined in article 2 verse (1) is the fulfillment of the normative- theological  aspects.  The  fulfillment  of the obligations  of both the obligation  is registering  the marriages  as noted in article  2 verse2 for the compliance of the normative aspects-sociological- juridical. The fulfillment of the obligations of both aspects is the main purpose of Article 2 verse (1) and verse (2) of Law No. 1 of 1974 about Marriage.  Thus, the dualism of unregistered marriage in Indonesia basically  is resolved. A marriage  is a legal action if it  fulfills  the elements  of religion  and marriage  registration procedures  based  on the  rules  that  have  been  specified  in the legislation.  The first element  has the function  as the legitimate sign and the second element serves the sign of a legal action which has any legal consequences. Marriage which is not recorded and has no legitimation  has not yet obtained legal consequences. The meaning  is the  unregistered  marriage or the  marriage  which is not recorded will automatically not considered as illegal action in Islamic law, besides the unregistered marriage is also not legal in the applicable law in Indonesia.